Claim modeling and insurance premium pricing under a bonus-malus system in motor insurance - Ieosanurak, Weenakorn; Khomkham, Banphatree; Moumeesri, Adisak (Zielona Góra: Uniwersytet Zielonogórski)
Accurately modeling claims data and determining appropriate insurance premiums are vital responsibilities for non-life insurance firms. This article presents novel models for claims that offer improved precision in fitting claim data, both in terms of claim frequency and severity. Specifically, we suggest the Poisson-GaL distribution for claim frequency and the exponential-GaL distribution for claim severity.
Keywords: bonus-malus system; claim severity; exponential-GaL distribution; motor insurance; number of claims; Poisson-GaL distribution